Identifikasi Dan Psikoterapi Terhadap ADHD: Attention Deficit Hyperactivity Disorder - Evita Yuliatul Wahidah (Al-Lubab : Jurnal Penelitian Pendidikan dan Keagamaan Islam, 2016)
ADHD, or Attention Deficit Hyperactivity Disorder more commonly known as hyperactivity. ADHD is a long-term disorder that strikes millions of children with symptoms that can last until adulthood. Anyone likely to suffer from ADHD, but these conditions are commonly experienced by people with learning disorders. Some of the symptoms experienced in the behavior of ADHD include difficulty concentrating, and the emergence of hyperactive and impulsive behavior. The symptoms of ADHD are generally visible from an early age and tend to be more pronounced when there is a change in the situation around the child, for example, began studying at the school. Most cases of ADHD detected at the age of 6-12 years. Children with ADHD tend to be low self-esteem, difficulty making friends, and having inadequate achievement.The symptoms of ADHD often decreases with age, but there are also people with ADHD who still experience it into adulthood. However, there are several methods that can be studied in order that these symptoms can be controlled. Some measures taken include medician, behavioral therapy and social interaction therapy. In this paper begins by examining on the definition of ADHD, continued the causes and identification, as well as the last of psychotherapy deals with ADHD.Keywords: Identification, Psychotherapy, ADHD (Attention Deficit Hyperactivity Disorder)